Institutional Quality Assurance: Reforming the Learning Management Framework in a Secular Academic Environment - Muhammad Haidlor; Moch Imam Machfudi; Najiburrohman Najiburrohman (JURNAL AL-TANZIM, 2026)
Higher education increasingly requires effective quality assurance systems to sustain learning governance and institutional performance amid evolving educational demands. This study aims to examine how institutional quality assurance reforms the learning management framework within a secular academic environment through integrated governance practices. A qualitative case study employing a descriptive-interpretive approach involved 35 purposively selected informants, with data collected through semi-structured interviews, non-participant observations, and document analysis, followed by interactive thematic analysis. The findings reveal that integrated management strengthened cross-unit collaboration, continuous evaluation fostered an organizational learning culture, and institutional quality assurance enhanced evidence-based learning governance through systematic planning, monitoring, and continuous improvement. The study proposes an integrated institutional governance framework that extends quality assurance beyond accreditation compliance. These findings provide practical guidance for university leaders to strengthen sustainable academic quality through collaborative governance, continuous evaluation, and evidence-based institutional decision-making.